Significance of pathohistological findings and the expression of Bcl-2 in diagnosis and treatment of oral planocellular carcinoma - Lončarević Slobodan; Vignjević Sanja; Jović Nebojša; Aćimović Ljubiša; Gardašević Milka; Todorović Vera; Dimitrijević Jovan (Vojnosanitetski Pregled)
Background/Aim. Numerous studies were aimed to detect and characterize various tumor markers in patients with oral planocellular carcinoma in order to reduce moratlity and mobidity rates of these patients, as well as to establish the correlation between the expression of specific tumor marker and prognostic outcome. The aim of this study was to determine patohistological characteristics of tumor and peritumor tissue in patients with oral planocellular carcinoma, with special regard to the expression of Bcl-2, as well as to point out the significance of clinicomorphological correlations for clinical use. Methods. Sixty-two patients with oral planocellular carcinoma, stage II and III, were examined. The patients were surgically treated for this condition at the Clinic for Maxillofacial Surgery, Military Medical Academy, Belgrade. Surgical specimens were obtained from both tumor and peritumoral tissues. Patohistologic degree of tumor differentiation and the immunohistochemical expression of Bcl-2 were determinated for each specimens. Results. Twenty-four (39%) patients had tumor dimension T1, while six (9%) and thirty-two (52%) patients had tumor dimension T2 and T3, respectively. Patohistologic analysis of peritumor connective, fat, muscle and bone tissue samples confirmed the presence of tumor infiltration. The expression of Bcl-2 in peritumor tissue samples correlated significantly with tumor’s histologic grade (ς = 0.468; p < 0.001), nuclear grade (ς = 0.430; p < 0.001) and nucleocytoplasmic ratio (ς = 0.410; p = 0.001). Conclusion. This results suggest that the expression of Bcl-2 in combination with patohistologic findings could have a prognostic value in patients with oral planocellular carcinoma.